Peran Kelompok Kerja Kepala Sekolah (K3S) dalam Menyukseskan Kebijakan Kurikulum Merdeka: Studi Kasus di Sekolah Dasar Negeri Kabupaten Banjar - Mirnawati, Sri; Suriansyah, Ahmad; Purwanti, Ratna (Equilibrium: Jurnal Pendidikan, 2025)
The implementation of the Independent Curriculum requires strong collaboration between education stakeholders, including the principal as a learning leader. This study aims to analyze the role of the Principal Working Group (K3S) in making the Independent Curriculum policy a success in Public Elementary Schools in Banjar Regency. The method used is a descriptive qualitative approach with a case study type. Primary data was obtained through interviews, participatory observations, and documentation of K3S activities, which were analyzed using thematic analysis techniques. The results of the study indicate that K3S plays an active role as a coordination forum, organizer of independent training, and a liaison between schools and the education office, although it still faces challenges such as competency gaps and limited external training. The implications of this study emphasize the importance of institutional strengthening and systematic assistance to K3S in order to encourage the effectiveness of the implementation of the Independent Curriculum evenly at the elementary school level.